2015
DOI: 10.4238/2015.january.16.8
|View full text |Cite
|
Sign up to set email alerts
|

Indirect selection of industrial tomato genotypes that are resistant to spider mites (Tetranychus urticae)

Abstract: ABSTRACT. Acyl sugars present in the tomato Solanum lycopersicum 'LA-716' accession confer good levels of resistance to arthropod pests. The objective of the present study was to select F 2 plants from the interspecific cross Solanum pennellii 'LA-716' x Solanum lycopersicum 'Redenção' to assess resistance to spider mites (Tetranychus urticae) based on the leaf acyl sugar content and repellence tests. Four genotypes were selected with high leaflet acyl sugar content (RVTA-2010 pl#31, RVTA-2010 pl#75, RVTA-201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…However, Resende et al (2009) found no significant correlation between AS content and whitefly oviposition rates, but did find a significant negative correlation between AS levels and the number of nymphs. Baier et al (2015) reported significant negative correlations between AS levels and the number of spider mites on tomato plants after 60 min of exposure to the mites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Resende et al (2009) found no significant correlation between AS content and whitefly oviposition rates, but did find a significant negative correlation between AS levels and the number of nymphs. Baier et al (2015) reported significant negative correlations between AS levels and the number of spider mites on tomato plants after 60 min of exposure to the mites.…”
Section: Discussionmentioning
confidence: 99%
“…Tomato genotypes of the F 2 generation (Baier et al, 2015) with different AS levels. These genotypes, together with the F 1 hybrid (S. lycopersicum 'Redenção' x S. pennellii LA-716), were cloned using their axillary rooting buds in 60-cell plastic trays that were filled with a commercial substrate and grown in a greenhouse.…”
Section: Whitefly Resistance Test In F 2 Tomato Genotypesmentioning
confidence: 99%
See 1 more Smart Citation
“…High heritability indicates that most of the variation among F 2 plants is due to genetics, suggesting the possibility of gains by selecting individuals with high content of ZGB in segregating populations. High heritability values are commonly estimated for allelochemical contents in plants from interspecific crosses, as reported by Baier et al, (2015) for acylsugar (h² = 81.8%), by Freitas (2002) for ZGB (h² = 67.8%), and Barbosa and Maluf (1996) for 2-tridecanone (h² = 60%).…”
Section: Resultsmentioning
confidence: 99%
“…This allelochemical has been found to be responsible for the resistance to several arthropod pests, including tetranychid mites (Resende et al, 2002;Maluf et al, 2007;Alba et al, 2009;Baier et al, 2015;Lucini et al, 2015). Sobreira et al (2009) have reported the occurrence of large genetic variability among cherry tomato accessions.…”
Section: Continued On Next Pagementioning
confidence: 99%